2011
DOI: 10.3415/vcot-10-03-0039
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis of Labrador Retrievers and Rottweilers trotting on a treadmill

Abstract: Both breeds had similar kinematic patterns, but there were magnitude differences, especially of the elbow and stifle joints. Therefore, each breed should have a specific database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 23 publications
0
64
1
Order By: Relevance
“…The stifle angle, in addition to tibial slope and sum of loading, is one of the important factors for the joint stability related to the direction of the compressive, ground reaction and ATT forces (Slocum and Devine, ; Boudrieau, ; Hashemi et al., ). Stifle kinematic angles have been recorded between 144° and 165° in dogs (Hottinger et al., ; Griffon, ; Ragetly et al., , ; Agostinho et al., ; Miqueleto et al., ), and 167° and 169° in humans (Nagano et al., ; Gaudreault et al., ; Robbins et al., ). If the bow angle is added to stifle joint angle, the angle will be between 162° and 183° in dogs and between 172° and 174° in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stifle angle, in addition to tibial slope and sum of loading, is one of the important factors for the joint stability related to the direction of the compressive, ground reaction and ATT forces (Slocum and Devine, ; Boudrieau, ; Hashemi et al., ). Stifle kinematic angles have been recorded between 144° and 165° in dogs (Hottinger et al., ; Griffon, ; Ragetly et al., , ; Agostinho et al., ; Miqueleto et al., ), and 167° and 169° in humans (Nagano et al., ; Gaudreault et al., ; Robbins et al., ). If the bow angle is added to stifle joint angle, the angle will be between 162° and 183° in dogs and between 172° and 174° in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The stifle joint angle is also different between dogs and humans in both, standing position and the stance phase of walking. The stifle joint has the maximum angle between 144° and 165° during the stance phase of walking for normal dogs, depending on breed (Hottinger et al., ; Griffon, ; Ragetly et al., , ; Agostinho et al., ; Miqueleto et al., ), while the knee joint angle is between 167° and 169° at the initial contact or early stance phase in humans (Nagano et al., ; Gaudreault et al., ; Robbins et al., ). This angle is measured in sagittal plane, based on the mechanical axes of the femur and tibia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used a two-dimensional space; other studies of canine gait used two (2D) and three-dimensional (3D) spaces (Colborne et al 2005, Agostinho et al 2011. These studies claimed that minor differences are noted between 2D and 3D analyze, many similarities exist between studies in two and three dimensions, such as the joint excursion curves joint and the range of motion, but one must be careful when making comparisons because there is a big difference in technology used for the collection and analysis of data from the studies already published .Can also be observed in studies with three-dimensional analysis kinematics in horses, this analysis has allowed the measurement of the angular range of flexion and extension movement metacaropophalangeal (Back et al 1993, Bennet et al 1996, Barrey 1997, Barrey 1999, König & Liebich 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The consolidation period after a DO was investigated in a 20-year retrospective study, based on 115 animals submitted to a corticotomy and application of a circular external fixator [2]. The authors concluded that the radius requires less time to consolidate than the tibia and presented the hypothesis that this occurs due to during the march, the radius bears weight in a parallel axis and the tibia carries the weight through an oblique axis [40]. Another hypothesis is based on the fact that dogs bear around 60% of their weight on the thoracic limbs, therefore the weight carried by a radius is superior to what is supported by a tibia [41][42][43].…”
Section: Consolidation Periodmentioning
confidence: 99%